Penatalaksanaan Fisioterapi Pada Kasus Post Dislokasi Elbow Dextra Di RSUD Panembahan Senopati Bantul - Sari, Nur Fadhilah, Wahyuni, S.Fis.,Ftr., M.Kes (2015)
Background: dextra elbow dislocation is a shift from the surface of the bone caused by attraction of the capsule. Conditions of elbow dislocation can be given to the reduction of manual actions and maintained by the gips with the elbow flexed 90 degrees for 3 weeks. And this situation can cause pain conditions, limitations LGS, decrease in muscle strength, and functional impairment. Objective: To pinpoint the benefits of Infrared, Massage. Exercise therapy, and index woodsrock to mengurnagi pain, improve LGS, increase muscle strength, and improve the functional condition of elbow dislocation dextra post. Results: From the results obtained therapy concluded that the decrease in VAS pain from T0 to T6 can be seen, tenderness T0 (2.5) to T6 (0), pain motion T0 (3.5) to T6 (0). Increased LGS with Goneometer from T0 to T6 with the results, actively T0 = S (0-50-120), R (50-0-70) became T6 = S (0-10-130), R (60-0-70), in passive T0 = S (050-125), R (50-0-75) became T6 = S (0-10-135), R (65-0-75). Increased muscle strength with MMT with the results, flexion T0 (3-) to T6 (3), the extension motion T0 (3-) to T6 (3), supination motion T0 (3-) to T6 (3), pronation motion T0 (3-) to T6 (3). Conclusion: Infrared, Massage, Therapeutic Exercise, and Index woodsrock can reduce pain, improve LGS, increase muscle strength.